2016
DOI: 10.1186/s12891-016-0914-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes after arthroscopic surgery compared to physical therapy for femoracetabular impingement: A protocol for a randomized clinical trial

Abstract: BackgroundAs the prevalence of hip pathology in the younger athletic population rises, the medical community continues to investigate effective intervention options. Femoracetabular impingement is the morphologically abnormal articulation of the femoral head against the acetabulum, and often implicated in pre-arthritic hip conditions of musculoskeletal nature. Arthroscopic surgical decompression and non-surgical rehabilitation programs focused on strengthening and stability are common interventions. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Postoperative rehabilitation was begun within 7 days; patients attended physical therapy for the first 7 weeks and then performed a detailed series of exercises 3 to 5 times per week. 43 Rehabilitation was typically completed within 6 months after surgery.…”
Section: Details Of Operative Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative rehabilitation was begun within 7 days; patients attended physical therapy for the first 7 weeks and then performed a detailed series of exercises 3 to 5 times per week. 43 Rehabilitation was typically completed within 6 months after surgery.…”
Section: Details Of Operative Treatmentmentioning
confidence: 99%
“…In the study conducted by Mansell et al, 43 a supervised physical therapy program comprising two 45-minute sessions twice per week for 6 weeks was provided. A personalized treatment plan was developed based on physical assessment; therapy included stretching, motor control exercises, and mobility exercises that were provided in detail in a series of handouts.…”
Section: Details Of Nonoperative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopy is the most common surgical procedure for FAI involving acetabuloplasty, labral repair/debridement, and/or femoroplasty [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because the apparent efficacy of surgery for alleviating symptomatic FAI and labral tears has been demonstrated in many noncomparative studies, 1,3,5,9,11,14 patients and surgeons usually expect the option to proceed to surgery if the nonsurgical treatment does not seem to be working. 2,20 One such trial that compared arthroscopic and nonsurgical treatment of FAI, done in a military setting by Mansell and colleagues, 12,13 appeared in AJSM last year and garnered considerable reader attention. 7,19 Mansell et al 13 reported no difference between the 2 alternatives in their intention-to-treat analysis.…”
mentioning
confidence: 99%